Transforming the narrative and visual reliefs of the Ramayana at Panataran Temple into comic media using a practice-based research approach - Alfan Setyawan; Raudah el Firdausiah Azzahra (Gelar: Jurnal Seni Budaya, 2025)
This study examines the transformation of the Ramayana reliefs at Panataran Temple into comic book form using a practice-based research approach. The focus of the study is to transform the reliefs into a comic book format while retaining the original narrative and visual elements of the reliefs in an effort to preserve their original cultural meaning. The methods used include iconographic analysis, character design, panel composition, color symbolism, and story structure. The results of the research are comics that integrate narrative and relief visuals, providing a new aesthetic experience for readers. The research contributes to the understanding of cultural representation through popular media, where comics are able to present attractive visual narratives of the Ramayana relief as a medium for preserving the culture of the archipelago.